Peningkatan Ketahanan Pangan Dan Gizi Masyarakat Era Covid 19 Pendekatan Strategi Pemasaran Dan Kepemimpinan Humanis Di Taman Darmaga Permai Rt 005/003 Desa Cihideung Hilir Kecamatan Ciampea Kabupaten Bogor - Sujana, Sujana; Maulana, Muhammad Iqbal (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Humanist leadership plays an important role in solving the problems of stagnant committee activities and organizations. Starting from a sincere intention from within a humanist is not looking for a living from the activity, but instead lives the activity, spends more time, more personal money comes out compared to funds from the organization, sacrifices more feelings than when not taking an approach humanist leadership, to innovate more in inviting residents to join and take an active part in activities including also inviting residents to spend more funds in helping to finance projects or public facilities from residents.